Math model for integrated bunker management in liner shipping - Li, Wenxuan (Nanyang Technological University, 2022)
Bunker cost is a major contributor to operating cost in the shipping industry. However, bunker price is volatile in nature and in the presence of ongoing regional conflicts and political tensions, it has reached new record highs recently. Thus, it is of great importance for shipping companies to minimize bunker cost. Many existing studies about this topic focused on one or two factors affecting bunker cost. Therefore, to fill the research gap, the aim of this paper is to discuss how different variables affect total bunker cost in liner shipping and to build a relatively holistic math model to assist liner shipping companies in reducing bunker cost. First, there is a brief introduction to bunker management, including procurement and operation. Secondly, I analyse several relevant research papers. Then the relationship among various factors and how they impact bunker cost are discussed. Finally I develop the math expression for total bunker cost including all the factors mentioned. This paper can provide foundation for deeper research on a cost-oriented bunker management system.